2011
DOI: 10.4103/0377-4929.77382
|View full text |Cite
|
Sign up to set email alerts
|

Malignant solid pseudopapillary tumor of pancreas causing sinistral portal hypertension

Abstract: Solid pseudopapillary tumor (SPT) of the pancreas is a rare benign or low-grade malignant epithelial tumor that occurs mainly in young females in second to fourth decades of life. Pathologic and imaging findings include a well-defined, encapsulated pancreatic mass with cystic and solid components with evidence of hemorrhage. We report a 23-year-old female who presented with upper abdominal pain of long duration and epigastric mass on palpation. Multidetector-row CT (MDCT) demonstrated a large well-defined hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
7
0
3
Order By: Relevance
“…Although there has been a steady increase in the number of diagnosed SPT cases globally, in India, only seven case reports describing 26 cases of SPTs are published [ Table 1]. [3,[5][6][7][8][9][10] All the cases reported were females, aged between 13 and 50 years. Pain in abdomen and painless abdominal lump were the commonest presenting symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…Although there has been a steady increase in the number of diagnosed SPT cases globally, in India, only seven case reports describing 26 cases of SPTs are published [ Table 1]. [3,[5][6][7][8][9][10] All the cases reported were females, aged between 13 and 50 years. Pain in abdomen and painless abdominal lump were the commonest presenting symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…Kamat et al reported a case of SPT followed for 3 years without significant change in size of the tumor [11]. Rarely, SPTs can present with splenic vein thrombosis with sinistral portal hypertension [12]. No laboratory values are contributory and some cases can have elevated Ca 19-9 levels [6].…”
Section: Discussionmentioning
confidence: 99%
“…However, not many case reports have been documented where surgery has been performed on cases with sinistral portal hypertension. One case report by Wani et al describes a case of malignant SPT treated by exploratory laparotomy and excision with splenectomy [4] . Ours is the first report on a benign SPT with sinistral hypertension treated with distal pancreatectomy.…”
Section: Discussionmentioning
confidence: 99%